A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam - Pham, Cuong The; Le, Minh Duc; Nguyen, Tao Thien; Ziegler, Thomas; Wu, Zheng Jun; Nguyen, Truong Quang (Zootaxa, 2017)
A new species of Limnonectes is described from northeastern Vietnam based on morphological and molecular differences. Morphologically, the new species is distinguishable from its congeners on the basis of a combination of the following diagnostic characters: Large size (SVL 50.1–68.9 in males, 45.5–63.0 mm in females); males with moderately enlarged head (HL/SVL 0.48), head longer than wide; vomerine teeth present; external vocal sacs absent; rostral length short (RL/SVL 0.16 in males, 0.15 in females); tympanum distinct (TD/ED 0.63 in males, 0.60 in females); dorsal surface of head, body and flanks with flattened tubercles; dorsal surface of tibia possessing small tubercles; supratympanic fold present; dorsolateral fold absent; webbing formula I0–0II0–1/3III0–1/3IV1/2–0V; in life, dorsum yellowish brown with a dark brown marking; throat and chest white with dark brown marking; ventral surface of fore and hind limbs as well as belly white. In phylogenetic analyses, the new species is placed as the sister taxon to Limnonectes fujianensis with strong statistical support in all analyses.